2010
DOI: 10.2134/agronj2010.0062
|View full text |Cite
|
Sign up to set email alerts
|

Genotype × Environment Interactions for Grain Yield in Rainfed Winter Wheat Multi‐Environment Trials in Iran

Abstract: Genotype × environment (G × E) interaction analysis was investigated on grain yield of 20 winter wheat genotypes grown in 24 environments in cold winter areas of Iran during 3 yr. Cluster and biplot analyses were applied to separate testing environments into groups with the same top‐yielding genotypes. Environment followed by G × E interaction effects accounted for the greatest proportion of the variability of grain yield of winter wheat genotypes. Cluster analysis divided both genotypes and environments into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…This result was similar to studies in which environmental effects were shown to be responsible for approximately 80% or more of the total experimental variation in wheat grain yield (Atlin and McRae 1994;Mohammadi et al 2010;Tapley et al 2013). Gauch and Zobel (1997) reported that locations accounted for approximately 80% of total variation, whereas genotype and G×E interactions each accounted for approximately 10%.…”
Section: Discussionsupporting
confidence: 87%
“…This result was similar to studies in which environmental effects were shown to be responsible for approximately 80% or more of the total experimental variation in wheat grain yield (Atlin and McRae 1994;Mohammadi et al 2010;Tapley et al 2013). Gauch and Zobel (1997) reported that locations accounted for approximately 80% of total variation, whereas genotype and G×E interactions each accounted for approximately 10%.…”
Section: Discussionsupporting
confidence: 87%
“…The wheat growing environment has a significant impact on the yield. The production of wheat requires high-quality soil; thus, the best available soil should be selected when growing wheat [36][37][38][39][40]. Farmers who do not have access to valuable soils may consider growing other agricultural crops to increase production efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we utilize data from the Oklahoma Small Grains Variety Performance Tests, a multienvironment trial, conducted yearly by Oklahoma State University (OSU). Most multienvironment trials focus mainly on yield (Kaya et al., 2006; Mohammadi et al., 2010; Roozeboom et al., 2008; Sukumaran et al., 2017) as this is one of the more important outcomes of a cultivar, for which producers base their choice. Yet, yield data alone provide limited insight into the mechanisms for differential responses of genetic cultivars to changing environments.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental effects, different genotypes, and genotype × environment (G × E) interactions play an important role in explaining yield variability (Mohammadi et al., 2010; Roozeboom et al., 2008). Specifically, G × E effects on wheat yield are ultimately driven by different physiological mechanisms.…”
Section: Introductionmentioning
confidence: 99%